Pre-existing Alloreactive T and B Cells and Their Possible Relevance for Pre-transplant Risk Estimation in Kidney Transplant Recipients - Karahan, Gonca E.; Claas, Frans H. J.; Heidt, Sebastiaan (Frontiers in Medicine, 2020)
In allogeneic transplantation, genetic disparities between patient and donor may lead to cellular and humoral immune responses mediated by both naïve and memory alloreactive cells of the adaptive immune system. This review will focus on alloreactive T and B cells with emphasis on the memory compartment, their role in relation to kidney rejection, and in vitro assays to detect these alloreactive cells. Finally, the potential additional value of utilizing donor-specific memory T and B cell assays supplementary to current routine pre-transplant risk assessment of kidney transplant recipients will be discussed.